Minimally invasive surgery versus open surgery for total pancreatectomy: a bibliometric review and meta-analysis - Wei, Kongyuan; Cheng, Luying; Zheng, Qingyong; Tian, Jinhui; Liu, Rong; Hackert, Thilo (HPB, 2023)
Background - Minimally invasive total pancreatectomy (MITP) is considered safe and feasible with limited evidence on this procedure. The aim of this study was to systematically analyze the current literature on MITP compared to open TP (OTP). - Method - Randomized controlled trials and prospective non-randomized comparative studies were sought systematically in MEDLINE, Web of Science and CENTRAL from their inception until December 2021. Outcome measures included operative time, length of hospital stay (LOH), spleen-preservation rate, estimated blood loss (EBL), need for transfusion, venous resection rate, delayed gastric emptying (DGE), biliary leakage, postpancreatectomy hemorrhage (PPH), reoperation rate, overall 30-day morbidity (Clavien-Dindo > IIIa), 90-day mortality, 90-day readmission, examined lymph nodes (ELN). Pooled results are presented as odds ratios (OR) or mean difference (MD) with 95% confidence interval (CI). - Results - 7 observational studies with a total of 4212 patients were included. MITP had a decreased EBL and transfusion rate, lower 30-day morbidity and 90-day mortality with a longer LOH compared to OTP. There were no significant differences regarding operative time, spleen preservation rate, DGE, biliary leakage, venous resection rate, PPH, reoperation, 90-day readmission and ELN. - Discussion - Based on the available studies, MITP is safe and feasible compared to OTP in highly experienced hands from high-volume centers. Further high-quality studies are needed to verify the conclusion.
Online verfügbar: 9. Februar 2023, Artikelversion: 14. Juni 2023
Gesehen am 02.08.2023